Mortality Patterns in the Medical Wards of Murtala Muhammad Specialist Hospital, Kano, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Introduction:The pattern of morbidity and mortality varies from region to region and reflects the burden of disease in a particular community. The knowledge of the pattern of diseases and their contribution to mortality in a given country is very important in evaluating its health care delivery system. This study determined the mortality pattern in the medical wards of Murtala Muhammad Specialist Hospital (MMSH), a tertiary health institution in North-western Nigeria.Materials and Methods:This is a retrospective study that reviewed the causes of death in the medical wards of the hospital between January 2013 and December 2015 (3 years). The admission and discharge registers of the medical wards between the stated period were retrieved and relevant data were reviewed and analyzed using Statistical Package for the Social Sciences version 19 software.Results:A total of 4834 patients admitted into the medical wards within the study period were analyzed. Of these, 3465 (71.7%) were discharged, referred, or discharged against medical advice and 1368 patients died, giving an overall mortality rate of 28.3%. The male to female admission ratio was 1.1:1, while the male to female death ratio was 1.5:1. Majority of deaths, 116 (81.7%), occurred after 24 h of admission. The most important causes of death were cerebrovascular disease (34.4%), sepsis (12.1%), congestive heart failure (11.6%), diabetes mellitus-related complications (8.9%), and chronic liver disease (8.6%).Conclusions:Mortality in the medical wards reflects the shift in the disease spectrum burden from communicable to noncommunicable diseases. Public health education, raising the socioeconomic status of our people as well as improving the standards of our health care facilities and personnel would prevent a large proportion of deaths from medical wards.